Outcomes of Transurethral Resection of the Prostate in Benign Prostatic Hyperplasia Comparing Prostate Size of more than 80 Grams to Prostate Size less than 80 Grams - Joshi, HN; de Jong, IJ; Karmacharya, RM; Shrestha, B; Shrestha, R (Kathmandu University Medical Journal, 2015)
Background Benign prostatic hyperplasia is a condition occurring in elderly men in which the prostate gland is enlarged, hence the condition also known as benign enlargement of prostate. Benign hyperplasia can lead to both obstructive and irritative symptoms. Transurethral resection of prostate (TURP) still remains the gold standard modality of surgical treatment of obstructive lower urinary tract symptoms due to Benign hyperplasia.Objectives The objective of this study was to evaluate the outcomes of TURP in large prostate (>80 grams) in comparison to small prostate (